DEFINITION OF POLES OF THE LARGE CIRCLES OF METEORIC TRAJECTORIES - Gorbanev, Yu. M.; Golubaev, A. V. (Одеські астрономічні публікації, 2009)
We present the method and software Meteor Pole for calculation of the spherical equatorial coordinates of the meteor points within the images obtained by TV observations. This software is a part of computer package Odessa Meteor which was elaborated for processing of the TV meteor patrol observational material. The results of such processing are the equatorial coordinates of the large circles poles of meteor trajectories on celestial sphere. These data are necessary for determination of the equatorial coordinates of radiants. We give the description of the method which enables one to estimate accuracy of the equatorial coordinates deternination taking into account specific chatcter of the operation of TV camera WATEC LCL-902 and its modifications. An analysis of the distribution of the large circles poles based on observations that were carried out in Astronomical Observatory of Odessa National University is given. We made a conclusion that there is no selected global direction in meteor movement on celestial sphere.